Treatment Satisfaction and Perceived Barriers among Patients with Social Health Insurance Scheme Utilization in a Hospital, Banke, Nepal - Kayastha, Shrijana; Ghimire, Gita Devi (Journal of Nursing and Health Sciences Nepal, 2024)
Introduction: Social health insurance is a mechanism for financing and purchasing / delivering health care to workers in the formal sector regulated by the government (Government of Nepal, 2013). This study aims to assess the satisfaction among patients (beneficiaries) utilizing social health insurance scheme and association with selected demographic variables.Methods: A cross-sectional descriptive research design was used to collect the data from 100 patients utilizing social health insurance scheme in a Hospital, Banke through purposive sampling technique. Short Assessment of Patient Satisfaction (SAPS) scale for measuring patients’ satisfaction was used for data collection through Face-to-face interview technique. The collected data were analyzed by using descriptive and inferential statistics.Results: The mean age of the respondents was 51.39±17.95 and majority (70.0%) of respondents were literate. The majorities (87.0%) of the respondents were satisfied and only 13.0% were dissatisfied with health services utilizing with social health insurance scheme. Forty percent of respondents felt too short time spent with doctors during treatment. Perceived barriers on waiting time in hospital was 58% while utilizing services under social health insurance scheme, followed by, delay in registration, procedure, laboratory reports, and less availability of needed medicine respectively. There is no statistically significant association between socio demographic characteristics and respondents’ satisfaction on treatment utilizing social health insurance scheme.Conclusions: The study finding reveals that the majority of respondents are satisfied with treatment in spite of experiencing some difficulties while utilizing social health insurance scheme. The health system or institution should devise to overcome the barriers of utilizing health insurance that can add more satisfaction in future.